Temporal and Spatial Variation of Potential Evaporation and Its Influencing Factors in Pearl River Basin from 1980 to 2019 - ZUO Daxing; ZANG Chuanfu; WANG Lina (Renmin Zhujiang)
Evaporation is an important link in the water cycle,and in-depth studies on the influence of various meteorological factors on evaporation changes are of great significance for climate change,ecological restoration,and utilization of water resources.In this study,the Penman-Monteith model modified by the Food and Agriculture Organization of the United Nations (FAO) is used to calculate the potential evaporation (ET0) in the Pearl River Basin from 1980 to 2019.The Mann-Kendall non-parametric test method and inverse distance weighting method are used to analyze the spatial and temporal distribution characteristics of the ET0,and the principal component analysis method is used to analyze the influencing factors.The results show that:① The average ET0 of the Pearl River Basin is 1 145.8 mm,and the growth rate is 1.37mm/a,which shows an increasing trend.In terms of four seasons,the growth rate increases in spring (0.56 mm/a),autumn (0.4 mm/a),and winter (0.44 mm/a) but decreases in summer (-0.03 mm/a).② In terms of spatial distribution,the annual average ET0 of the Pearl River Basin is high in the east,west,and south but low in the middle andnorth.The distribution of ET0 in summer,autumn,and winter is similar.However,the distribution of ET0 in spring is opposite to that in summer,autumn,and winter.③ Temperature,average water vapor pressure,and altitude are the leading factors of ET0 changes.Factors such as temperature,average water vapor pressure,sunshine duration,and wind speed make positive contributions to ET0,while altitude,latitude,and relative humidity make negative contributions to ET0 changes.